How do natural soil NH4+, NO3− and N2O interact in response to nitrogen input in different climatic zones? A global meta‐analysis. (28th May 2021) - Zheng, Xiang; Liu, Qi; Ji, Xiaofang; Cao, Minmin; Zhang, Yuefang; Jiang, Jiang
Abstract: The increase of fossil‐fuel burning and nitrogen (N) fertilizer consumption continues to elevate global N deposition, leading to significant increases of soil NH4 + and NO3 − concentrations, and thus N2 O emissions. This is especially important for natural, unmanaged soils which are considered as areas that are sensitive to N input. However, uncertainties exist regarding the interactions of soil N2 O emissions with soil NH4 + and NO3 − concentrations in response to N input in different climatic regions, as well as their underlying potential mechanisms. Here, we conducted a meta‐analysis to investigate the responses of these three forms of N to external N input across global natural ecosystems, using data extracted from peer‐reviewed studies. The results show that soil NO3 − concentrations are increased to a much larger extent by N input in temperate regions (136%) compared to tropical (62%) and subtropical (54%) regions, whereas the increase of soil NH4 + concentrations by N input is much less than soil NO3 − concentrations, at 20%, 26% and 28% in temperate, tropical and subtropical regions, respectively. The significantly larger increase in soil NO3 − concentrations but slightly lower increase in soil NH4 + concentrations in temperate regions compared to other climatic zones may be ascribed to the dominant nitrification process in temperate areas, which promotes the conversion of NH4 + to NO3 − . Soil N2 O emissions were increased to the greatest extent in subtropical regions (348%) in response to N input, followed by temperate regions (111%) and tropical regions (44%), which may be a result of the dominant denitrification process in subtropical regions, which promotes N2 O production. It is likely that denitrification also dominates N2 O production in tropical regions, but the dampened effect of N input on stimulating soil N2 O emissions in these areas suggests that the loss of NO3 − substrate due to intensive leaching might be an important issue. This study could provide a better understanding of the heterogeneous risks of soil N responses in different climatic zones in the context of increasing global N deposition. Highlights: Larger N input‐induced increases in soil NO3 − concentrations in temperate regions may derive from increased nitrification. Larger N input‐induced increases in soil N2 O emissions in subtropical regions may derive from increased denitrification. Less increase in soil N2 O emissions in tropical regions after N input may be due to heavy precipitation‐induced NO3 − leaching. Soil N2 O emissions in subtropical regions may be more sensitive to increased N input compared to other climatic zones.